Reinventing Philippine governance for globalization. - Cariño, Ledivina V.; Briones; Leonor M.; Florano, Ebinezer R.; Follosco, Kristine C. (Philippine Journal of Public Administration)
Globalization is the "buzzword" in today's world and it has brought unprecedented impacts to the Asia Pacific region including the Philippines. The Philippines, although political unequipped has optimistically joined the "bandwagon" and is now struggling to reinvent its governance to cope with international and national pressures on globalization. Among these are the complexities and challenges in managing national affairs, institutionalization issues on globalization and the difficulties in reaping the fruits of participation and accountability. This article centers on two themes: the public sector capacity of the country to manage globalization, and participation and accountability in globalization. The role of the private sector and civil society in coming up with innovations and new approaches to deal with the changed situations is given emphasis. The article also tackles the policy implications of globalization and the lessons learned in the Philippines and in Asia at large.